Media Digital dan Pendekatan Saintifik: Membangun Kesadaran Lingkungan di SDN 060970 Medan Belawan - Dekar, Muhammad; Widyastika, Dinda; Wahyudi, Dichi Akbar; Ramadhan, Teuku Muhmmad Hary; Armanda, Fahmy; Ritongga, Nazla (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study was to examine how the environmental awareness of third-grade students at SD Negeri 060970 Medan Belawan was influenced by a scientific approach focused on character education and digital-based interactive media. A 2 × 2 factorial design was used in the experimental methodology of this study. One hundred students were selected as the research sample using a simple random sampling method. An environmental awareness test instrument that had undergone validity and reliability testing was used to collect data. After successfully completing the normality and homogeneity tests, data analysis was conducted using a two-way ANOVA at a significance level of 0.05. The research findings indicated that: (1) students' environmental awareness was significantly influenced by a scientific approach focused on character education; (2) students' environmental awareness was significantly influenced by interactive digital media; and (3) there was a significant interaction between the scientific approach and digital media. The highest level of environmental awareness was achieved when both were combined. Therefore, it is recommended that digital media and a character-based scientific approach be combined as an efficient teaching method to help elementary school students develop their environmental awareness.